Strengthening disease surveillance in Nigeria: A systematic review of performance evidence across IDSR, SORMAS, and DHIS2 platforms - Vivian Nwechi; Augustine Usman Adaka; Maryam Abubakar Umar; Ibukunoluwa Foluso Akinola; Ammar Auwal Abdullahi; Polycarp Dauda Madaki; Zainab Bello Dambazau (Journal of Interventional Epidemiology and Public Health, 2026)
Introduction: Nigeria experiences recurrent outbreaks of infectious diseases, yet the performance of its disease surveillance systems across different platforms and disease programmes has not been systematically synthesized. This systematic review identified, appraised, and synthesised published evidence on the performance of disease surveillance systems in Nigeria using the CDC 2001 surveillance evaluation framework. Methods: Five electronic databases and grey literature sources were searched for studies published between 2001 and 2025 that evaluated disease surveillance systems in Nigeria. Two reviewers independently screened records, extracted data, and appraised methodological quality using JBI checklists and the Mixed Methods Appraisal Tool. A narrative synthesis was conducted, and findings were organised by CDC 2001 attributes, disease category, surveillance platform, and geopolitical zone. Results: Twenty-nine studies met the inclusion criteria, with 93.1% (27/29) rated as high quality. AFP/poliomyelitis surveillance demonstrated consistently high performance on timeliness (98-100%), sensitivity (non-polio AFP rates: 4.5-55.2 per 100,000), and completeness (97-100%), while tuberculosis and NTD surveillance showed substantially lower sensitivity (17.6-25.0%) and PPV (12.7-20.3%). Electronic platforms (eIDSR and SORMAS) were associated with improved timeliness (73% vs. 43%) and completeness (≥85% vs. ≤65%) compared to paper-based systems. Persistent barriers included private sector exclusion (reporting rates as low as 3.9%), donor dependency, resource constraints, and insecurity. Representativeness was the most frequently reported attribute (100%), while sensitivity (40%) and PPV (20%) were least reported. Conclusion: Nigerian surveillance systems show heterogeneous performance, with vertical programmes outperforming broader IDSR systems. Sustainable government funding, private-sector integration, and digital platform scale-up are urgently needed to strengthen national surveillance.